(untitled) (Journal of Educational Sciences, 2017)
In the article the description of the national games, which are based on ethnic Kazakh mentality. The main emphasis is on the content of the national games and their connection with the usual ethnic life of the Kazakh people. It also describes in detail the connection between the two concepts: national games and national customs. A detailed explanation is given of each game, which is popular among the adult population. Described, and children’s national game, they have not lost their value and popularity in the present time. States that the purpose of education in the modern world must conform to ideas of preservation of our cultural and spiritual heritage, ethnoethics of the nation. According to this justifies the significance of the study of psychology as applied to the individual, the family, the traditions of the past and present that should be passed down from generation to generation.The culture of the people associated with the priceless heritage of national literature. According to the authors, people must not only be strong physically to handle the burden of the nomadic way of life they have to be strong mentally. Nomads were hunters, men who were soldiers, and shepherds, were the pillar of the family. In this aspect, the national games have raised not only the mood in the difficult conditions of life, but also supported the unity of the spirit and body. National games have educational, military, sports, ethno-traditional, communicative and artistic-aesthetic character. They performed the tasks of physical training, the development of mental abilities of young people.